Multiscale study of fracture in aluminum-magnesium alloy under fatigue and dynamic loading (Fracture and Structural Integrity, 2015)
In this paper we investigated the influence of consecutive dynamic and gigacycle fatigue loads on the lifetime of aluminum-magnesium alloy AlMg6. Preloading of samples was achieved during dynamic tensile tests in the split-Hopkinson bar device. Fatigue tests were conducted on Shimadzu USF-2000 ultrasonic fatigue testing machine. This machine provides 109-1010 loading cycles with the amplitude from 1 to several dozens of microns and frequency of 20 kHz, which reduces dramatically the testing time in the comparison to the classical fatigue testing machines. The New-View 5010 interferometer–profiler of high structural resolution (resolution of 0.1 nm) was used for qualitative fracture surface analysis, which provided the data allowing us to find correlation between mechanical properties and scale-invariant characteristics of damage induced roughness formed under dynamic and gigacycle fatigue loading conditions.Original form of the kinetic equation was proposed, which links the rate of the fatigue crack growth and the stress intensity factor using the scale invariant parameters of fracture surface roughness. The scale invariancecharacterizes the correlated behavior of multiscale damage provides the link of crack growth kinetics and thepower exponent of the modified Paris law.
Keywords: Fractal analysis